Investigation of an Egyptian Mummy board by Using Clinical Multi-slice Computed Tomography. (3rd October 2018) - Longo, Sveva; Mormina, Enricomaria; Granata, Francesca; Mallamace, Domenico; Longo, Marcello; Capuani, Silvia
ABSTRACT: A modern approach to the diagnosis of artistic heritage makes use of non-destructive techniques which avoid damage to artworks or signs of interaction with the analytical technique used. For this reason, today, the employment of X-rays to study artistic heritage is quite widespread. Computed tomography (CT) Imaging was first used as specialized medical diagnostic tool in the early 1970s. Today, CT scanners have become more common, and non-destructive three-dimensional imaging has found an increasing number of uses in different areas such as materials research, geology, archaeology, and museum conservation. In this work, a new generation of clinical CT (based on the Dual Energy and multi-slice acquisition principle) is used to investigate an Egyptian wooden mummy board with a total acquisition time of 93.23 seconds and a voxel size of 0.078 × 0.078 × 1.5 mm. The use of two distinct techniques of image post-processing, the two-dimensional multi-planar reconstruction (MPR) and the three-dimensional volume rendering technique (VRT) allowed us to: evaluate the state of conservation of the mummy board, determine how the wooden object was implemented, recognize a nineteenth-century intervention of consolidation, and advance the hypothesis that the wooden planks were reused. In particular, we highlight the use of the cardiovascular and pulmonary filter with VRT reconstruction, which allows a virtual elimination of different parts of the mummy board to investigate those areas otherwise accessible only by removing parts of the board and thus damaging the work. GRAPHICAL ABSTRACT: